2009
DOI: 10.1002/sia.3074
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coupling agent chain lengths on interfacial performances of carbon fiber and polyarylacetylene resin composites

Abstract: The influence of chain lengths on interfacial performances of carbon fiber/polyarylacetylene composites was studied. For this purpose, four coupling agents, methyltrimethoxysilane, propyltrimethoxysilane, octyltrimethoxysilane and dodecyltrimethoxysilane, were grafted onto fiber surface to obtain different chain lengths. The resulting carbon fiber surface was characterized by XPS and dynamic contact angle test. Interfacial adhesion in the resulting fiber reinforced polyarylacetylene resin composites was also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…One of the most effective methods is by coating the carbon fibers with a ductile polymeric material to modify the mode of failure and thus the potential energy absorbing capacity of their composites [5][6][7]. However, many researches showed that thin coatings were finite in toughening the composites whereas thick coatings resulted in the reduction of composite strength and modulus [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective methods is by coating the carbon fibers with a ductile polymeric material to modify the mode of failure and thus the potential energy absorbing capacity of their composites [5][6][7]. However, many researches showed that thin coatings were finite in toughening the composites whereas thick coatings resulted in the reduction of composite strength and modulus [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…These entanglements are fixed by polymer-resin curing. As a result, long chains on the fiber surface produce strong chain interactions at the composite interface 55) . Hussain et al 56) demonstrated that the hydrocarbon chains plasticize and improve the compatibility of the inorganic particle to the epoxy when titanate is bonded to an inorganic filler.…”
Section: Effect Of Chain Length Of the Coupling Agentmentioning
confidence: 99%
“…This result could be attributed to the better hydrophobicity of TCA than silane because of its long hydrocarbon chain that could provide a stable interfacial bond in humid environments, thereby increasing toughness. Jiang et al 47 reported that chain lengths significantly influence interfacial adhesion in composites. Long-chains on the fiber surface also augment the interfacial shear strength.…”
Section: Effect Of Sbf Exposure On Fracture Toughnessmentioning
confidence: 99%